Non-random aneuploidy specifies subgroups of pilocytic astrocytoma and correlates with older age - Fontebasso, Adam; Hutter, Barbara; Şeker-Cin, Huriye; Witt, Hendrik; Pfister, Stefan; Jones, David T. W. (OncoTarget, 2015)
Pilocytic astrocytoma (PA) is the most common brain tumor in children but is rare in adults, and hence poorly studied in this age group. We investigated 222 PA and report increased aneuploidy in older patients. Aneuploid genomes were identified in 45% of adult compared with 17% of pediatric PA. Gains were non-random, favoring chromosomes 5, 7, 6 and 11 in order of frequency, and preferentially affecting non-cerebellar PA and tumors with BRAF V600E mutations and not with KIAA1549-BRAF fusions or FGFR1 mutations. Aneuploid PA differentially expressed genes involved in CNS development, the unfolded protein response, and regulators of genomic stability and the cell cycle (MDM2, PLK2),whose correlated programs were overexpressed specifically in aneuploid PA compared to other glial tumors. Thus, convergence of pathways affecting the cell cycle and genomic stability may favor aneuploidy in PA, possibly representing an additional molecular driver in older patients with this brain tumor.